Closed-loop supply chain coalitional cooperation and coordination under differentiated carbon tax regulation. (15th March 2023) - Yu, Zhongwei; Lin, Yang; Wang, Yingming; Goh, Mark
Abstract: This paper presents a systematic two-stage analysis to improve a three-echelon closed-loop supply chain cooperation and coordination under differentiated carbon tax regulation, which enriches non-cooperative and cooperative game theory applications in remanufacturing circular economies. Firstly, we utilize non-cooperative games to explore the optimal operations of new and remanufactured products across five coalitional models. Then, we adopt cooperative games to achieve profit coordination. Specifically, Shapley values are employed for allocating a grand coalition profit in a centralized setting. In order to alleviate carbon taxpayers' fairness concerns, we proposed a novel revised Shapley value algorithm incorporating differentiated carbon tax costs to improve their utility. The results show that regulators can reduce emissions by adjusting carbon tax rates on different products more effectively. The optimal environmental and economic performance can also be achieved by forming a grand coalition. Shapley value algorithms achieve the supply chain system Pareto improvement. Moreover, carbon taxpayers' (i.e., manufacturer and remanufacturer) utilities in our revised Shapley are improved by 20.15% and 77.71%, respectively, compared with the classical Shapley value under certain conditions. These results benefit regulators' carbon tax policy formulation and industrial managers' remanufacturing practices. Graphical abstract: Image 1 Highlights: Construct a two-stage analysis for remanufacturing cooperation and coordination. Apply non-cooperative games to derive optimal results of five coalition models. The impact of the differentiated carbon tax on supply chain operations is examined. Cooperative games allocate supply chain channel profit in a centralized setting. Revised Shapley value algorithm alleviates carbon taxpayers' fairness concerns.